Pengujian Antena Yagi Grid Extreme Sebagai Alat Penguat Sinyal Di Desa Tebat Benawa - Dedi Setiadi; Asep Syaputra (Jurnal Teknik Komputer AMIK BSI, 2023)
The village of Tebat Benawa, the city of Pagar Alam, is located in a highland surrounded by many hills and trees. This is one of the factors that causes the signal emitted by the Base Tranceiver Station (BTS) tower which is ±12 km to the village of Tebat Benawa to be less good. Therefore, to improve the quality of the wifi network in the village of Tebat Benawa by utilizing the yagi grid extreme antenna as a signal amplifier. In this study, the Prepare, Plan, Design, Implemant, Operate, Optimaze (PPDIOO) method is used, because in this method there are steps that can assist in improving the quality of the wifi network by using an extreme yagi grid antenna in the village of Tebat Benawa. Prior to the installation of the Yagi Grid Extreme antenna, the wifi signal strength obtained was 2.1 Kbps, which means the signal strength is in the E or EDGE (Enchance Data Rate for GSM Eolution) signal range, which means that data transfer is slow. In measurements after using the Yagi Grid Extreme antenna, the signal strength in a closed room was obtained with a value of -32 dBm with a speed of 80 Mbps, but when the user's range was 20 meters from the antenna, the wifi signal strength became -89 dBm with a speed of 19 Mbps. While the test when the antenna is installed outside with a support pole, the wifi signal strength is -23 dBm and the speed is 72 Mbps, which means the signal is in the excellent or very good category.